2011
DOI: 10.18061/dsq.v31i2.1588
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionality Among Postsecondary Students Seeking Evaluation to Document Disabilities

Abstract: <p>The race/ethnicity disproportionality in identification of special education disability classifications in K-12 education and psychological disorders in the general population has been explored for many years. Other disproportionality trends exist in postsecondary enrollment. However, there is little exploration of the convergence of these phenomena and the representation of students with disabilities in postsecondary education disability service programs. Longitudinal data collected at an evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…It is possible that these students, like their counterparts at community colleges, are attracted to the small classes and individual attention provided by private, liberal arts colleges. It is also possible, however, that these students and their families possess the academic savvy and financial resources necessary to pursue disability testing and to gain access to academic accommodations not afforded their peers (Anyon, 2009; Pellegrino, Sermons, & Shaver, 2011).…”
Section: Students With Disabilities At Selective Private Collegesmentioning
confidence: 99%
“…It is possible that these students, like their counterparts at community colleges, are attracted to the small classes and individual attention provided by private, liberal arts colleges. It is also possible, however, that these students and their families possess the academic savvy and financial resources necessary to pursue disability testing and to gain access to academic accommodations not afforded their peers (Anyon, 2009; Pellegrino, Sermons, & Shaver, 2011).…”
Section: Students With Disabilities At Selective Private Collegesmentioning
confidence: 99%
“…Data from this study showed that these students were assigned to vocational tracks despite students' expressed desire to attend college. An additional study by Pellegrino, Sermons, and Shaver (2011) provided evidence demonstrating the underrepresentation of African American students with disabilities seeking evaluation documentation for postsecondary accommodations. Their data findings also lend evidence to the possibility that "K-12 personnel may be steering college-able minority students toward alternatives to college preparation in diploma tracks due to their disability rather than an actual lack of academic ability" (Pellegrino et al, 2011).…”
Section: Barriers Encountered By African American Students With Disabilitiesmentioning
confidence: 99%
“…The existing scholarship on multiply-marginalized dis/abled Black and Brown students in higher education has primarily focused on the experiences of Black students who identify or were labeled as dis/abled. Research has documented that Black students with dis/abilities encounter several barriers in transitioning to colleges and universities including inequitable access (Oesterreich & Knight, 2008), lack of resources for transitioning from high school to college (Durodoye et al, 2004), and underrepresentation in seeking evaluation for dis/abilities on college campuses (Pellegrino et al, 2011). Even prior to attending college, Black students labeled with dis/abilities encounter numerous barriers including an increased likelihood of being placed into restrictive educational settings such as separate special education classrooms, decreased access to rigorous curriculum including gifted and talented programs, and higher suspension and expulsion rates (Blanchett, 2006; Harry & Klingner, 2014; National Center for Learning Disabilities, 2020; Skiba et al, 2006).…”
Section: Multiply-marginalized Black and Brown Students In Higher Edu...mentioning
confidence: 99%